IMPLEMENTATION OF MOVING AVERAGE FILTER FOR THE MONITORING WATER LEVEL IN WATER TANKS USING ANTARES. - Raffi Noval Pambudi; Slamet Indriyanto; Sigit Pramono (Journal of Electronic and Electrical Power Applications, 2022)
Almost all monitoring systems for measuring the height of water reservoirs use ultrasonic sensors. One of the ultrasonic sensors that is already waterproof is the JSN-SR04T ultrasonic sensor. However, this sensor has a weakness, namely the high error rate of sensor readings, thereby reducing the accuracy of sensor readings. One way to reduce errors that occur in sensors is to implement a Moving Average Filter (MAF) data filter. The MAF used in this study are MAF 5 and MAF 10. The purpose of this study is to test the sensor by comparing the sensor error value if not using MAF by using MAF 5 and MAF 10. For the monitoring system and the database of sensor measurement results used in this study is to use the Antares platform. The test results of the JSN-SR04T ultrasonic sensor reading value state that if the sensor does not use MAF, the sensor reading value produces an average error of 5.41%. Then if the sensor uses MAF 5 produces an average error of 3.42% and MAF 10 produces an average error of 5.21%. These results prove that the implementation of the Moving Average Filter is able to reduce the JSN-SR04T ultrasonic sensor reading error.